In Silico Studies of Khellin and Related Furochromenes by Modified POM Analysis - Renata Gašparová (Chemistry Proceedings, 2024)
POM (Petra/Osiris/Molinspiration) analysis and related in silico tools are well-established methods used to evaluate the potential of molecules to become drug candidates by predicting their biological activity and calculating various physicochemical properties, ADME parameters, or toxicity. Khellin 1 is a well-known component of the Ammi visnaga (khella) plant used for centuries in folk medicine for the treatment of urinary tract pain associated with kidney stones. Modern medicine has found the importance of khellin in the treatment of psoriasis, angina pectoris, or vitiligo. However, the oral use of khellin is limited by its potential adverse effects, such as dizziness, constipation, headache, itching, or lack of appetite. Many natural or synthetic furopyrrole derivatives have been extensively studied and reported to possess numerous biological effects, including anticancer, anti-inflammatory, or antimicrobial. The present in silico study is aimed at revealing the most promising drug candidates based on favorable pharmacokinetic parameters and toxicological characteristics. A modified POM analysis of sixteen furochromenes was performed using Molinspiration, Osiris, and SwissADME software. Studied structures were selected due to the modifications of the khellin skeleton. Substitution of the furan or pyran ring, modification of one or both methoxy groups, or hydrogenation of one or both heterocyclic rings were included. The results of this preliminary in silico investigation suggest all furopyrroles have good oral bioavailability and a high level of gastrointestinal absorption. The bioactivity score prediction shows their ability to act predominantly as ion channel modulators or enzyme inhibitors. All compounds exhibit a low risk of being irritants; nine of them exhibit a low risk of being mutagenic, tumorigenic, or having reproductive effects.